Prediction of live body weight from linear body measurements in sheep breeds of Botswana - KAELO PELOTSHWEU; MONOSI A. BOLOWE; NICODEMUS P. MOSWEU; KETSHEPHAONE THUTWA; PATRICK M. KGWATALALA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pelotshweu K, Bolowe MA, Mosweu NP, Thutwa K, Kgwatalala PM. 2025. Prediction of live body weight from linear body measurements in sheep breeds of Botswana. Biodiversitas 26: 2696-2705. Phenotypic correlation data serve as a baseline to predict the outcomes of selection, which can in turn be used to inform appropriate conservation and breed improvement programs and strategies. Therefore, the study aimed to determine phenotypic correlations between body weight and morphometric traits and develop body weight prediction equations using morphometric traits for different sheep (Ovis aries) breeds in Botswana. Phenotypic correlation coefficients were determined from 595 sheep (Damara: 79, Dorper: 177, Karakul: 135, Meat-master: 156; Tswana: 48). Prediction equations were estimated from 94 sheep (Damara: 20, Dorper: 30, Karakul: 16, Meat-master: 28) using Stepwise regression procedures of Statistical Analysis System (SAS) 9.4. The highest positive significant (p<0.05) correlation coefficients were found between body weight and heart girth in both sexes across different sheep breeds. Males had higher correlation coefficients than females, except for Karakul males. Body length was more positively correlated (r: 0.81, 0.79, and 0.97) with body weight than height at withers (r: 0.78, 0.44, and 0.08) in Dorper, Meat-master, and Tswana male sheep, respectively. Morphometric traits like heart girth, body length, height at withers, neck length, cannon bone length, cannon bone circumference, and scrotal circumference in males were used for the prediction of body weight in Dorper, Damara, Meat-master, and Karakul sheep. Heart girth accounted for more variability in the prediction model for both sexes of all breeds, except for Damara males, where it was coupled with body length to predict their body weight. This indicates that body weight can be indirectly selected through selection for heart girth, height at withers, and body length. The study shows that heart girth, height at withers, and body length are the main traits that can be used in prediction equations of different sheep breeds to estimate body weight in the absence of weighing scales.